Locus of Control and Economic Decision-Making: A Field Experiment in Odisha, India - Jansson, Cecilia Ahsan; Patil, Vikram; Vecci, Joseph; Chellattan Veettil, Prakashan; Yashodha (The University of Chicago Press, 2025)
We study psychological impediments that make it difficult to change behavior. In particular, we evaluate the effect of a randomized intervention designed to target locus of control—an individual’s belief in his or her own ability to influence his or her outcomes—on the adoption of two products that can improve climate resilience. In the control group, farmers receive standard agricultural education. Treatment farmers are assigned to one of three treatments. They receive agricultural training and (1) a psychological information treatment providing tools to change beliefs about one’s sense of control, (2) a crop-simulation app allowing farmers to simulate their agricultural decisions, or (3) both treatments combined. Our sample consists of 1,674 farmers from 252 villages in Odisha, India. At baseline, we find that most individuals do not believe they can influence their agricultural outcomes. However, the interventions show limited effect on agricultural behavior, locus of control, or aspirations. We then explore potential explanations for these findings.